2023
DOI: 10.1002/adfm.202211735
|View full text |Cite
|
Sign up to set email alerts
|

Responsive Spiral Photonic Structures for Visible Vapor Sensing, Pattern Transformation and Encryption

Abstract: Two photon polymerisation using direct laser writing is a burgeoning field of research, with recent focus being placed on bringing added value to microstructures, by incorporating soft, responsive polymers. Moving to the micron‐scale can have a profound impact on such stimuli‐responsive materials, whose speed of actuation can be increased many‐fold compared to their mm‐scale counterparts. Here, the fabrication of submicron 2D photonic structures, based on a vapor‐responsive photoresist with a refractive index … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 71 publications
0
15
0
Order By: Relevance
“…Apart from the aforementioned stimuli, other external stimuli, including stress [233,234], solvent [235,236], and electric field [237][238][239], can also be used to trigger the dynamic behaviors of intelligent stimulus-responsive structures manufactured by FsLDW technology. For instance, Gräf et al demonstrated the mechanically sensitive surface structural color of LIPSS-based diffraction gratings on ductile austenitic stainless steel through FsLDW.…”
Section: Other Stimulus-responsive Structuresmentioning
confidence: 99%
“…Apart from the aforementioned stimuli, other external stimuli, including stress [233,234], solvent [235,236], and electric field [237][238][239], can also be used to trigger the dynamic behaviors of intelligent stimulus-responsive structures manufactured by FsLDW technology. For instance, Gräf et al demonstrated the mechanically sensitive surface structural color of LIPSS-based diffraction gratings on ductile austenitic stainless steel through FsLDW.…”
Section: Other Stimulus-responsive Structuresmentioning
confidence: 99%
“…Figure 3. Consecutive vapor response testing [6]. a) S1 (25 mW laser power), b) S2 (27.5 mW laser power) and c) S3 (30 mW) as a function of exposure time at peak (dotted line) and trough (solid line), respectively.…”
Section: Applications 31 Vapor Sensingmentioning
confidence: 99%
“…Figure 4 Color pixels design and encryption pattern [6]. a) Schematic of 5L spiral photonic structure design with a 0.6 µm thick film underneath (d = 0.5 µm, g1 = g2 = g3 = 2.5 µm).…”
Section: Pattern Encryptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the optical characteristics of visible light and their interaction with a variety of external stimuli have been deeply explored to elevate encryption levels. [16][17][18] Therefore, the search for new forms of information encryption and the building of corresponding materials are highly desirable.…”
Section: Introductionmentioning
confidence: 99%